Time-resolved photoluminescence study of CdSe/CdMnS/CdS core/multi-shell nanoplatelets - Murphy, J. R. (2016)
We used photoluminescence spectroscopy to resolve two emission features in CdSe/CdMnS/CdS and CdSe/CdS core/multi-shell nanoplatelet heterostructures. The photoluminescence from the magnetic sample has a positive circular polarization with a maximum centered at the position of the lower energy feature. The higher energy feature has a corresponding signature in the absorption spectrum; this is not the case for the low-energy feature. We have also studied the temporal evolution of these features using a pulsed-excitation/time-resolved photoluminescence technique to investigate their corresponding recombination channels. A model was used to analyze the temporal dynamics of the photoluminescence which yielded two distinct timescales associated with these recombination channels. The above results indicate that the low-energy feature is associated with recombination of electrons with holes localized at the core/shell interfaces; the high-energy feature, on the other hand, is excitonic in nature with the holes confined within the CdSe cores.